Acute and subacute toxicity evaluation of ethanol extract from aerial parts of Epigynum auritum in mice. (September 2019) - Yang, Meilian; Wu, Zihuan; Wang, Yudan; Kai, Guoyin; Singor Njateng, Guy Sedar; Cai, Shengbao; Cao, Jianxin; Cheng, Guiguang
Abstract: Acute and subacute toxicities of the ethanol extract from Epigynum auritum (EAE) wereperformed by oral administration in pathogen-free mice. Acute toxicity study was performed at a single dose of 5000 mg/kg for 14 consecutive days, while subacute toxicity test was conducted by daily oral administration of EAE at doses of 312, 625, 1250, and 2500 mg/kg for 28 days. Acute toxicity study showed that LD50 of EAE was over 5000 mg/kg. The results of subacute toxicity showed no significant adverse effect of EAE at 312 mg/kg. Moreover, EAE exhibited toxicities to liver, spleen and kidney in mice determined by hematological, serum biochemical and histological analyses during daily oral administration of 1250 mg/kg and 2500 mg/kg EAE. The results revealed that the dose of EAE lower than 625 mg/kg can be regarded as safe. Graphical abstract: Image 1 Highlights: Acute & subacute toxicity of ethanol extract from aerial parts of Epigynum auritum (EAE) were assessed. The LD50 of EAE was higher than 5000 mg/kg BW evaluated by acute toxicity. EAE can be regarded as practically non-toxic based on acute toxicity. EAE didn't show toxicity at 312 mg/kg by subchronic toxicity. EAE showed toxicities to some organs at 1250 mg/kg and 2500 mg/kg.